Upaya Pemerintah Kota Medan dalam Peningkatan Sistem Transportasi untuk Mengurangi Kemacetan (Studi Penelitian Underpass di Jalan H.M Yamin) - Pasaribu, Rizky Asriansyah; Nasution, Mahliza (Politeknik Negeri Lhokseumawe, 2025)
Traffic congestion has become one of the main issues faced by the city of Medan, in line with the growth of population and vehicles. The Medan City Government has taken various measures to address this issue through the development of transportation infrastructure, including the construction of underpasses at several strategic points, as well as the introduction of electric buses as an alternative mass transportation. Infrastructure development, such as the underpass on HM Yamin Street, has proven effective in reducing congestion in critical areas. Additionally, the operation of electric buses provides an environmentally friendly solution that can reduce the density of private vehicles and greenhouse gas emissions. This study aims to analyze the efforts of the Medan City Government in improving the transportation system and reducing traffic congestion through infrastructure projects and mass transportation. The results of the study show that these measures have a positive impact on traffic flow and travel time efficiency, although challenges remain related to the increasing volume of vehicles. In the future, the development of a more integrated mass transportation system is necessary to ensure the sustainability and long-term success of these effort.